2022
DOI: 10.3389/fcimb.2022.945000
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-dependent expression of type II secretion system controls extracellular product secretion and virulence in mesophilic Aeromonas salmonida SRW-OG1

Abstract: Aeromonas salmonicida is a typical cold water bacterial pathogen that causes furunculosis in many freshwater and marine fish species worldwide. In our previous study, the pathogenic A. salmonicida (SRW-OG1) was isolated from a warm water fish, Epinephelus coioides was genomics and transcriptomics analyzed. Type II secretion system was found in the genome of A. salmonicida SRW-OG1, while the expressions of tatA, tatB, and tatC were significantly affected by temperature stress. Also, sequence alignment analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…However, a wide infection caused by A. salmonicida has been reported in different species of fish worldwide, including rainbow trout ( Oncorhynchus mykiss ), Atlantic salmon ( Salmo salar ), arctic char ( Salvelinus alpinus ), brook trout ( Salvelinus fontinalis ), brown trout ( Salmo trutta ), carp ( Cyprinus carpio ), goldfish ( Carassius auratus ), orange‐spotted grouper ( Epinephelus coioiaes ) and sablefish ( Anoplopoma fimbria ) from Canada, USA, Switzerland, Norway, France, South Korea, Spain, Chile, China and so on (Bartkova et al, 2010; Charette et al, 2012; Evenberg et al, 1986; Huang, Qi, Zuo, Alias, & Xu, 2020; Humphrey & Ashburner, 1993; Pylkkö et al, 2005; Valderrama et al, 2019; Vasquez et al, 2020). In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020; Meng et al, 2020; Wang et al, 2020), pathogenicity (Chen et al, 2022; Meng et al, 2017; Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020; Long et al, 2015; Xia et al, 2022; Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a wide infection caused by A. salmonicida has been reported in different species of fish worldwide, including rainbow trout ( Oncorhynchus mykiss ), Atlantic salmon ( Salmo salar ), arctic char ( Salvelinus alpinus ), brook trout ( Salvelinus fontinalis ), brown trout ( Salmo trutta ), carp ( Cyprinus carpio ), goldfish ( Carassius auratus ), orange‐spotted grouper ( Epinephelus coioiaes ) and sablefish ( Anoplopoma fimbria ) from Canada, USA, Switzerland, Norway, France, South Korea, Spain, Chile, China and so on (Bartkova et al, 2010; Charette et al, 2012; Evenberg et al, 1986; Huang, Qi, Zuo, Alias, & Xu, 2020; Humphrey & Ashburner, 1993; Pylkkö et al, 2005; Valderrama et al, 2019; Vasquez et al, 2020). In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020; Meng et al, 2020; Wang et al, 2020), pathogenicity (Chen et al, 2022; Meng et al, 2017; Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020; Long et al, 2015; Xia et al, 2022; Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
Section: Introductionmentioning
confidence: 99%
“…. In particular, it is worth noting that, more and more studies in China on infection (Lian et al, 2020;Meng et al, 2020;Wang et al, 2020), pathogenicity (Chen et al, 2022;Meng et al, 2017;Yi et al, 2022) and interaction with hosts of A. salmonicida (Huang, Qi, Zuo, Alias, & Xu, 2020;Long et al, 2015;Xia et al, 2022;Xue et al, 2021) have been reported in recent years, implying the popularity and importance of this bacterium in China.…”
mentioning
confidence: 99%
“…The impact of temperature on the biofilm formation has been studied in several microbes including P. aeruginosa (Townsley and Yildiz, 2015;Townsley et al, 2016;Plumley et al, 2017;Kim et al, 2020;Almblad et al, 2021;del Peso Santos et al, 2021). Temperature is also known to cause stress in mesophilic pathogens found in cold water (Yi et al, 2022). Previous research has shown that temperature can indeed influence the gene expression and protein profile of P. aeruginosa at environmental versus host-associated temperatures (Bisht et al, 2021).…”
Section: Introductionmentioning
confidence: 99%